The duration and breadth of antibody responses to 3-dose of inactivated COVID-19 vaccinations in healthy blood donors: An observational study - Ou, Shanhai; Huang, Zehong; Lan, Miaoling; Ye, Jianghui; Chen, Jijin; Guo, Huilin; Xiao, Jin; Zhuang, Shucheng; Wu, Jiahuang; Yang, Chuanlai; Fang, Mujin; Su, Yingying; et al. (Frontiers in Immunology, 2022)
Objectives We aimed to evaluate the duration and breadth of antibodies elicited by inactivated COVID-19 vaccinations in healthy blood donors. Methods We performed serological tests on 1,417 samples from 658 blood donors who received two (n=357), or three (n=301) doses of COVID-19 inactivated vaccine. We also accessed the change in antibody response before and after booster vaccination in 94 participants and their neutralization breadth to the current variants after the booster. Results Following vaccination, for either the 2- or 3-dose, the neutralizing antibodies (nAbs) peaked with about 97% seropositivity approximately within one month but subsequently decreased over time. Of plasmas collected 6-8 months after the last immunization, the nAb seropositivities were 37% and 85% in populations with 2-dose and 3-dose vaccinations, respectively. The nAbs of plasma samples (collected between 2-6 weeks after the 3rd dose) from triple-vaccinated donors (n=94) showed a geometric mean titer of 145.3 (95% CI: 117.2 to 180.1) against the ancestral B.1, slightly reduced by 1.7-fold against Delta variant, but markedly decreased by 4-6 fold in neutralizing Omicron variants, including the sub-lineages of BA.1 (5.6-fold), BA.1.1 (6.0-fold), BA.2 (4.2-fold), B.2.12.1 (6.2-fold) and BA.4/5 (6.5-fold). Conclusion These findings suggested that the 3rd dose of inactivated COVID-19 vaccine prolongs the antibody duration in healthy populations, but the elicited-nAbs are less efficient in neutralizing circulating Omicron variants.